Promoting behavior changes in children: The role of care givers selfmonitoring behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
Behavioral education of caregivers, in various formats, has proved effective in promoting changes in children’s behavior. This experiment aimed to teach caregivers to use strategies of extinction and reinforcement, and to make functional analysis of behaviors to decrease the frequency of children’s inappropriate behaviors. Three of the five families concluded the whole program of self-monitoring and functional analysis of behavior training. For two of the three families who completed the whole program, inappropriate behavior’s remission was significant. For the third family, the changes were related to the mother’s comprehension about the child’s behavior before intervention. In all cases, self-monitoring played an important role serving as a control tool in an applied research context. The fourth and fifth family did not conclude the program due to the absence of written skills and due to problems in the availability to be part of the research.
Keywords: self-monitoring; appropriate behavior; inappropriate behavior; family intervention